ON RESISTANCE AND RESILIENCE TO HEGEMONIC POWER: A STUDY OF AMERICAN GUITAR REPLICAS IN INDONESIA - Jatmiko, Rahmawan (Rubikon : Journal of Transnational American Studies, 2026)
This article presents the results of a participation-based study conducted in Indonesia, focusing on the regions of Yogyakarta and Solo. Situated within the field of American Studies, the research adopts a postcolonial framework, particularly drawing on Homi K. Bhabha’s concept of mimicry in relation to multiculturalism and hybridity. The study primarily examines forms of resilience and resistance to hegemonizing power within the guitar industry and market in Indonesia, using counterfeit American-brand guitars, specifically those associated with Fender Musical Instruments Corporation, as its main object of analysis. This investigation focuses on the replica of two Fender company’s ever most widely used guitar products: the Stratocaster® and Telecaster® guitars. This research is somehow not dealing with the legal aspect of the counterfeiting practices, but it academically searches for and examines some proves underlying a premise that to imitate the hegemonizing power, which in certain circumstances is done illegally, might be considered as an instance and manifestation of resilience and resistance mainly performed by the hegemonized society in global capitalism. This can also be seen as the way the society sustains its existence, by performing adaptation or adjustment, and fighting back the hegemonizing power which is previously believed to be insurmountable.